1.75-(-3/8)+(0.5)-(-5/6) +4又2/3)-1/8
1个回答
1.75+(3/8)+0.5+(5/6)+4又2/3- 1/8
=2.25+2/8+5/6+28/6
=9/4+1/4+33/6
=10/4+33/6
=30/12+66/12
=96/12
=8
相关问题
计算:(+8)+(-23)+(-8)+(+23)=?1又3/4+(-6.5)+3又3/8+(-1.75)+2又5/8=?
3.75-[(-3/8)+(-1/2)-(-5/6)+4又3/2]-0.125
2.75-(-1/2)+(-5/6)-(-3/8)+4又1/3
6-1又5/8= 1又4/5÷18= 0.18×5/6= 0.75-1/4= 4-1又1/3= 7÷2又1/3= 2又1
1.(5.75-4.75)/[2.5+(0.75*1.25*8) 2.(6.9*3.6*3.5)/(1.25/0.25)
1又4分之3 +(-6.5)+3又8分之3+(-1.75)+2又8分之5
1/3+1/5 1-8/3 1/6-1/7 1/5+0.8 15又1/4-14 3又1/2+0.5 4-2又1/5 4又
5/17*(-3/7)+5/17*(-4/7)-12/17 (-0.75)*(-3又1/8)-0.75*(-4又7/8)
(-3)-(-5)+(-6)+3= -(+1.5)-(-4又4分之一)+3.75-(+8又2分之一
计算关于绝对值 -│ -2/1│= │-2/1│+│-3/4│= │-0.75│/│+5又8/5